Defining the composition and electronic structure of large-scale and single-crystalline like Cs2AgBiBr6 films fabricated by capillary-assisted dip-coating method. (June 2019) - Xiu, Jingwei; Shao, Yangfan; Chen, Linxun; Feng, Yue; Dai, Junfeng; Zhang, Xusheng; Lin, Yi; Zhu, Yudong; Wu, Zhenggang; Zheng, Yini; Pan, Hui; Liu, Chang; et al.
Abstract: Owning the merits of both lead-free and air-stable, the double-perovskite Cs2 AgBiBr6 has attracted increasing attention, but suffers low visible-light absorption coefficient due to its large indirect bandgap. Moreover, the electronic structure of its synthesized films has not been explored clearly yet. In this work, we developed a general and promising method to fabricate continuous, uniform and highly orientated Cs2 AgBiBr6 films in large scale on various substrates through capillary-assisted dip-coating method. Strikingly, those optimized films are single crystalline verified by φ-scan XRD. Its electronic structure was carefully studied independently by multi-photo-physical characterizations. Its bandgap can be tuned from 2.65 to 2.25 eV by changing the substrate temperature in growth from 40 to 160 °C. Essentially, their work-function (WF) was determined at −5.01 eV and WF-VBM is around 2 eV. This novel band structure with typical n-type characteristic, was further confirmed by DFT calculations, which reveals that the Cs interstitials and Br vacancies derived deep defect levels were fixed around its Fermi level, closer to the conduction band. This conclusion is different from its widely accepted p-type feature, but definitely deepens our understanding of this material and inspires us to find more valuable strategies of modulating its band structure and optoelectronic properties. Graphical abstract: Large scale and single crystalline like Cs2 AgBiBr6 films were successfully fabricated by Capillary-assisted Dip-Coating Method with tunable band gaps. Their electronic structure was entirely discovered and constructed. It is revealed that the Cs interstitials and Br vacancies derived deep defect levels were fixed around its Fermi level, which is closer to the conduction band and leads to n-type semiconducting characteristic.Image 1 Highlights: We developed a capillary-assisted dip-coating method to fabricate highly orientated Cs2 AgBiBr6 films on various substrates. Those optimized films are single crystalline verified by φ-scan XRD. Its electronic structure was entirely discovered and examined by a set of photo-physical characterizations independently. The Cs interstitials and Br vacancies derives deep defect levels and leads to n-type semiconducting characteristic.